Modelling the descent of nitric oxide during the elevated stratopause event of January 2013. (March 2017) - Orsolini, Yvan J.; Limpasuvan, Varavut; Pérot, Kristell; Espy, Patrick; Hibbins, Robert; Lossow, Stefan; Raaholt Larsson, Katarina; Murtagh, Donal
Abstract: Using simulations with a whole-atmosphere chemistry-climate model nudged by meteorological analyses, global satellite observations of nitrogen oxide (NO) and water vapour by the Sub-Millimetre Radiometer instrument (SMR), of temperature by the Microwave Limb Sounder (MLS), as well as local radar observations, this study examines the recent major stratospheric sudden warming accompanied by an elevated stratopause event (ESE) that occurred in January 2013. We examine dynamical processes during the ESE, including the role of planetary wave, gravity wave and tidal forcing on the initiation of the descent in the mesosphere-lower thermosphere (MLT) and its continuation throughout the mesosphere and stratosphere, as well as the impact of model eddy diffusion. We analyse the transport of NO and find the model underestimates the large descent of NO compared to SMR observations. We demonstrate that the discrepancy arises abruptly in the MLT region at a time when the resolved wave forcing and the planetary wave activity increase, just before the elevated stratopause reforms. The discrepancy persists despite doubling the model eddy diffusion. While the simulations reproduce an enhancement of the semi-diurnal tide following the onset of the 2013 SSW, corroborating new meteor radar observations at high northern latitudes over Trondheim (63.4°N), the modelled tidal contribution to the forcing of the mean meridional circulation and to the descent is a small portion of the resolved wave forcing, and lags it by about ten days. Highlights: Model simulations made during the elevated stratopause event in January 2013. Detailed comparison is made between model nitric oxide and satellite observations. Model underestimates descent of nitric oxide from the mesosphere-lower thermosphere. Planetary waves dominate the forcing as the stratopause reforms. Model semi-diurnal tide is amplified yet contributes little to forcing the descent.